(untitled) (Research, Society and Development, 2021)
This text is intended to be discussed in the implementation of the Itinerant Laboratory for the Teaching and Learning of Mathematics (LIEAM), linked to the Department of Human Sciences of the University of the State of Bahia, Campus IX, and its implications for the teaching and learning movements da Mathematics. The objective of LIEAM is to awaken the curiosity and interest of two students of Fundamental Education in Mathematics, from the use of games, enigmas and other potentially playful devices; Besides promoting, through the relationship between the university and the school, a study environment, teaching, research and mediated extension for itinerant activities. As analyzes, it is possible to observe that experiment spaces such as this relevant topic role in the formation of a teacher who teaches Mathematics, one time that the conduction of this space is (re) significance of their pedagogical practice. On the other hand, not that it has years of teaching and learning movements from science, is perceptible about an approach two students involved in Mathematics, or that it contributed to a demystification of the image of science as difficult and little accessible.